To find the expression \( 2B - 2C \) in standard form given
\[ B = 3x - x^2 \quad \text{and} \quad C = x - 8 - 8x^2 \]
we will first calculate \( 2B \) and \( 2C \).
- Calculate \( 2B \):
\[ 2B = 2(3x - x^2) = 6x - 2x^2 \]
- Calculate \( 2C \):
\[ 2C = 2(x - 8 - 8x^2) = 2x - 16 - 16x^2 \]
- Now, find \( 2B - 2C \):
\[ 2B - 2C = (6x - 2x^2) - (2x - 16 - 16x^2) \]
We distribute the negative sign through \( 2C \):
\[ = 6x - 2x^2 - 2x + 16 + 16x^2 \]
Now, combine like terms:
- For \( x \) terms: \( 6x - 2x = 4x \)
- For \( x^2 \) terms: \( -2x^2 + 16x^2 = 14x^2 \)
Thus, we have:
\[ 2B - 2C = 14x^2 + 4x + 16 \]
- Standard form:
The standard form of a polynomial is typically expressed in descending order of the powers of \( x \). Putting it all together, we express \( 2B - 2C \) as:
\[ \boxed{14x^2 + 4x + 16} \]